COMPLICATIONS OF TRACHEOSTOMY AND LEADING FACTORS AMONG PATIENTS PRESENTING AT A TERTIARY CARE HOSPITAL, KARACHI - Wasim, Muhammad Fahad; Riaz, Naeem; Aslam, Sohail; Bukhari, Syed Muhammad Asad Shabbir; Mumtaz, Humza; Ahmed, Waseem (Pakistan Armed Forces Medical Journal, 2021)
Objective: To look for the complications of tracheostomy and factors correlated with presence of these complications at a tertiary care teaching hospital of Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: ENT department, Operation Theater, Emergency department and Critical Care Unit of Pakistan Naval Ship Shifa Hospital, Karachi Pakistan, from Apr to Oct 2019.Methodology: Sixty nine patients who underwent tracheostomy were included in the analysis. Final decision regarding offering the procedure of tracheostomy to the patient was made by consultant ENT specialist in liaison with the primary treating physician. Patients were assessed for the complications during the procedure, immediately after the procedure, 48 hours after the procedure and one week after the procedure.Results: Out of sixty nine patients included in the study, 8 (11.6%) patients underwent emergency tracheostomy while 61 (88.4%) underwent elective tracheostomy. Ten (14.5%) had undergone percutaneous procedure while 59 (85.5%) had undergone open surgical procedure. Hemorrhage was the commonest complication reported followed by dislodgement. With Pearson chi-square test, we found that increasing age (45 years) and emergency tracheostomy had strong association with the presence of complications among the patients undergoing tracheostomy.Conclusion: Tracheostomy emerged as a safe procedure with mostly minor self-limiting complications. Surgeon performing this procedure should be aware of these common complications and should give information care to the patients prior to the procedure. Patients who are elderly or undergoing emergency tracheostomy should be dealt with special care while doing this life saving procedure.